PENGARUH KARAKTERISTIK PEKERJAAN, PEMBERIAN REWARD DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM (KSP). MAKMUR MANDIRI SUMBUL PEGAGAN KABUPATEN DAIRI - Bancin, Kristina; Simangunsong, Elisabeth; Sitanggang, Darna (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2023)
This research aims to determine the influence of job characteristics, reward provision and work environment on employee performance at KSP. Makmur Mandiri Sumbul Pegagan. Data collection was carried out through questionnaires, interviews and documentation. The research method used was quantitative, with 37 respondents taken using saturated sampling or census. The analysis techniques used in this research are validity and reliability testing, multiple linear regression, and hypothesis testing. Data analysis in this study used SPSS version 20. From the partial test results, job characteristics have a partially significant effect on employee performance. Likewise, giving rewards shows that rewards have a partially significant effect on employee performance. Furthermore, the t test on the work environment shows that the work environment has a partially significant effect on employee performance. The F test shows that job characteristics, rewards and work environment simultaneously have a significant effect on KSP employee performance. Makmur Mandiri Sumbul Pegagan The coefficient of determination is 0.773, meaning that employee performance can be explained by the variables of job characteristics, reward provision and work environment at 77.3% while another 22.7% is explained by other variables not included in this research.